Bloodstream Infection and Gram-Negative Resistance: The Role for Newer Antibiotics - Jessica Waters; Andrew F. Shorr (MDPI AG, 2023)
Gram-negative resistance remains a major challenge. Rates of in vitro resistance to commonly utilized antibiotics have skyrocketed over the last decade. Clinicians now encounter multidrug-resistant organisms routinely. Fortunately, newer agents, such as ceftazidime-avibactam, ceftolozone-tazobactam, meropenem-vaborbactam, and cefiderocol, have been developed and are now available for use against these pathogens. Clinical trials with these novel therapies have focused on multiple infection types ranging from complicated urinary tract infections to nosocomial pneumonia. Nonetheless, there remains little information about the efficacy of these drugs for bacteremia. To better appreciate the types and limitations of the evidence supporting the role for these unique molecules in bloodstream infection, one requires an appreciation of the initial clinical trials supporting the regulatory approval of these antibiotics. Furthermore, physicians must understand the subsequent case series and reports specifically focusing on outcomes for patients with bacteremia treated with these drugs. Despite the limitations of the data and reports relating to treatment for bacteremia with these antibiotics, each agent appears to be efficacious and can provide good outcomes in bloodstream infections due to resistant pathogens.